1995
DOI: 10.1071/pp9950585
|View full text |Cite
|
Sign up to set email alerts
|

Plant Regeneration and Microprojectile-Mediated Gene Transfer in Embryonic Leaflets of Peanut (Arachis hypogaea L.)

Abstract: Excised leaflets from mature embryos of peanut cultivars Robut, Gajah, McCubbin and NC-7 produced multiple shoot primordia via organogenesis on Murashige and Skoog medium supplemented with 3 mg L-1 BAP and 1 mg L-1 NAA. Plants were regenerated by elongation of shoot primordia on transfer to MS medium supplemented with 5 mg L-1 BAP. The regeneration frequency of five plants per embryonic leaflet was 10-40-fold higher than previously reported from seedling leaflets. Microprojectile bombardment parameters were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 28 publications
1
20
1
1
Order By: Relevance
“…The addition of kinetin to the GAs-containing medium further enhanced the number of elongated shoots. Livingstone and Birch (1995) observed substantial elongation of TDZ-derived shoots on 22.2 p.M BA medium, although the same concentration of BA did not bring about noticeable improvement in elongation of TDZ-derived peanut shoot primordia in our experiments. However, due to the inclusion of TDZ (1 gM) in the BA (22.2 l.tM)-supplemented medium, our results are not directly comparable with the previous report.…”
Section: Discussioncontrasting
confidence: 70%
“…The addition of kinetin to the GAs-containing medium further enhanced the number of elongated shoots. Livingstone and Birch (1995) observed substantial elongation of TDZ-derived shoots on 22.2 p.M BA medium, although the same concentration of BA did not bring about noticeable improvement in elongation of TDZ-derived peanut shoot primordia in our experiments. However, due to the inclusion of TDZ (1 gM) in the BA (22.2 l.tM)-supplemented medium, our results are not directly comparable with the previous report.…”
Section: Discussioncontrasting
confidence: 70%
“…Using 4-d IILC plated on similar medium, they found the shoot fre quency of fastigiate lines Tamnut 74 and UPL Pn-4 to be higher than that of NC 7. Livingstone and Birch (1995) used MS basal medium + 1 mg L" 1 NAA + 3 mg L" 1 BAP and found that 50% of nonimbibed leaflets of cv. Robut (subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Particle gun bombardm ent initially develop ed by Sanford and his group at Cornell University (Sanford et al, 1987;Klein et al, 1987) has been successfully used for direct introduction of genes into a variety of plant species (see Varsha et al, 1997) including peanut. Embryogenic callus (Ozias-A kins et al, 1993;Livingstone and Birch, 1997), zygotic embryos (Schnall and Weissinger, 1993) and embryonic leaflets (Livingstone and Birch, 1995) have been used for transfo rmation using particle gun bombardment in peanut. Transient gene expression as assayed by GUS assay was affected by both particle size and amount of DNA used for coating and was found to be positively correlated with gene copy number (Lacorte et al, 1997).…”
Section: Dir Ect Dna Tr Ans Fer Usin G Particl E Gun Bomb Ardm Entmentioning
confidence: 99%